PENERAPAN WEIGHTED K-MEANS DAN HEATMAP OVERLAY UNTUK REKOMENDASI LOKASI STRATEGIS UMKM KOPI KELILING: IMPLEMENTATION OF WEIGHTED K-MEANS AND HEATMAP OVERLAY FOR STRATEGIC LOCATION RECOMMENDATION OF MOBILE COFFEE MSMES - Ridho Alif Naufaldy; Asep Wahyudin; Herbert Siregar (LPPM Universitas Abdurrab, 2026)
Determining the operational routes for MSME mobile coffee vendors currently relies on subjective intuition, leading to time inefficiencies and income fluctuations. This study designs a mobile-based Decision Support System (DSS) using a Prototyping approach to provide objective strategic location recommendations. The system processes 10,961 historical transactions using the Weighted K-Means algorithm. Cluster center determination is modified using the center of mass principle based on profit and sales quantity weights, then visualized through a heatmap overlay. Functional testing using the Black Box method confirmed that all application parameters are valid. Field trials empirically demonstrated the system's effectiveness through a 16.6% surge in the fleet's average daily net profit (from Rp1,654,254 to Rp1,929,709). In conclusion, this DSS has proved to be successful in transforming conventional route determination into a data-driven precision strategy to boost MSME profitability.